Estructura y funcionamiento familiar y su incidencia en el desarrollo del lenguaje oral de los niños y niñas de primer grado de educación general básica de la unidad educativa “María Auxiliadora” de la ciudad de Cariamanga. Período lectivo 2013-2014. Lineamientos alternativos - Aguilar Velásquez, Adela Magdalena (2014)
This thesis called FAMILY STRUCTURE AND OPERATION AND ITS IMPACT ON BASIC GENERAL EDUCATION FIRST DEGREE CHILDREN ORAL LANGUAGE DEVELOPMENT "MARÍA AUXILIADORA" SCHOOL CARIAMANGA CITY. PERIOD 2013-2014. ALTERNATIVE GUIDELINES. It has been structured and developed in accordance with the Rules of Academic Board of the Loja National University. The general objective that guided the research was: To determine the incidence of family structure and Functioning. The methods used for the preparation of this research work were: Scientist, Deductive - Inductive, Descrptivo, and Analytical Model - Synthetic, the same that served effectively help to achieve the goal. The techniques and instruments used were: Survey to applied to children parents of Basic Education First year “María Auxiliadora” school, to set the Structure and Family Functioning. And a Guide Watching applied to children's school development said where it will conduct research aimed at the of oral language. From Parent’s survey applied concludes that 73% Parent that the child's family group consists of father, mother and children; 17% for mother and children; 5% by grandparents and grandchildren; 3% Uncles and nephews; and 2% of parents and children. 69% of Parents say the feature or mode of being of your family is stable; Rigid 15%; Overprotective 8%; Unstable 5%; and 3% Permissive According to the results of the observation guide the following result was obtained: 48% of children have a developing oral language Highly Satisfactory, Satisfactory 43%; and 9% Unsatisfactory.